Risk factors for target vessel endoleaks after physician-modified fenestrated or branched endovascular aortic arch repair: A retrospective study - Chen, Zhipeng; Fu, Dongsheng; Liu, Cheng; Jin, Yi; Pan, Chaohui; Mamateli, Subinur; Lv, Xiaochen; Qiao, Tong; Liu, Zhao (Frontiers in Cardiovascular Medicine, 2023)
Objective Fenestrated or branched endovascular aortic arch repair (fb-arch repair) is an effective option for treating complex aortic arch lesions, including thoracic aortic aneurysms and aortic dissections. However, the relatively high rate of re-intervention due to target vessel (TV)-related endoleaks have raised concerns. This study aimed to determine risk factors for TV-related endoleaks after fb-arch repair. Methods This was a retrospective analysis of all patients undergoing fb-arch repair between 2017 and 2021in nanjing drum tower hospital of China. All the patients underwent computed tomography angiography (CTA) before surgery; at discharge; and at 3 months, 6 months, and yearly post-discharge. All procedures are performed with physician modified grafts. Two experienced vascular surgeons used CTA and vascular angiography data to assess endoleaks. The study endpoints were mortality, aneurysm rupture, and emergence of and re-intervention for TV-related endoleaks. Results During the follow-up period, 218 patients underwent fb-arch repair. There were seven perioperative deaths and four deaths during follow-up (two myocardial infarctions and two malignancies). There were nine additional patients who were excluded from the study (two strokes, three with abnormal aortic arch anatomy, and four with insufficient clinical data). Among the 198 patients considered (mean age, 59 ± 13.3 years; 85% male), 309 branch arteries were revascularized. A total of 35 TV-related endoleaks were identified in 28 patients during a mean follow-up of 23 ± 14 months (median 23, IQR 26.3): six type Ic, 4 type IIIb, and 20 type IIIc endoleaks. Patients in the endoleak group had greater aortic arch segment diameters (43.1 ± 5.1 vs. 40.3 ± 4.7; P = 0.004) and a greater number of TVs revascularized (2.0 ± 0.8 vs. 1.5 ± 0.8; P = 0.004) than those in the non-endoleak group. However, the morphological classification of the aortic arch did not seem to affect the occurrence of TV endoleaks (13%, 14%, and 15% for type І, II, and III aortic arches, respectively; P = 0.957). Pre-sewing branch stents in the fenestration position reduced the risk of TV endoleaks (5% vs. 14%; P = 0.037). Additionally, in TVs affected by aortic aneurysm or dissection, the risk of endoleaks increased after reconstruction (17% vs. 8%; P = 0.018). The incidence of secondary TV-related endoleaks after fb-arch repair was 14.1%. Conclusion The data from this study showed that the incidence of secondary target vessel related endoleaks after fb-arch repair is approximately 14.1%. Additionally, patients with a larger aortic arch diameter or more revascularized arteries during surgery were at increased risk TV-related endoleaks. The target vessels originating from the false lumen or aneurysm sac are more prone to endoleaks after reconstruction. Finally, prefabricated branch stents reduced risk of TV-related endoleaks.